Enhanced photocatalytic activity against crystal violet dye of Co and In doped ZnO thin films grown on PEI flexible substrate under UV and sunlight irradiations. Issue 6 (June 2019) - Ben Ameur, S.; BelHadjltaief, H.; Duponchel, B.; Leroy, G.; Amlouk, M.; Guermazi, H.; Guermazi, S.
Abstract: This work is focused on the photocatalytic activities of undoped ZnO, Co (1%) doped ZnO (CZO) and In (1%) doped ZnO (IZO) thin films grown on flexible PEI (Polyetherimide) substrate by spray pyrolysis. The photodegradation of crystal violet dye was investigated under UV and sunlight irradiations. Doping and excitation energy effects on photocatalytic efficiencies are discussed. All ZnO thin films show high photocatalytic efficiency up to 80% under either UV or sunlight irradiations for 210 min. However, CZO has the higher photocatalytic performance under UV irradiation. While, the photodegradation efficiency of IZO was enhanced under sunlight irradiation due to the narrowing of its optical gap. These results are discussed based on structural, morphological and optical investigations. The photocatalytic stability of ZnO films was studied as well. So, after three photocatalysis cycles, all ZnO thin films still effective. The obtained results are promising for the use of doped ZnO/PEI as talented photocatalysts for applications in large surfaces with various geometries for photodegradation of hazardous pollutants.